Lenalidomide enhances antitumor functions of chimeric antigen receptor modified T cells - Otáhal, Pavel; Průková, Dana; Král, Vlastimil; Fabry, Milan; Vočková, Petra; Latečková, Lucie; Trněný, Marek; Klener, Pavel (Oncoimmunology, 2016)
Tumor immunotherapy based on the use of chimeric antigen receptor modified T cells (CAR T cells) is a promising approach for the treatment of refractory hematological malignancies. However, a robust response mediated by CAR T cells is observed only in a minority of patients and the expansion and persistence of CAR T cells in vivo is mostly unpredictable.Lenalidomide (LEN) is an immunomodulatory drug currently approved for the treatment of multiple myeloma (MM) and mantle cell lymphoma, while it is clinically tested in the therapy of diffuse large B-cell lymphoma of activated B cell immunophenotype. LEN was shown to increase antitumor immune responses at least partially by modulating the activity of E3 ubiquitin ligase Cereblon, which leads to increased ubiquitinylation of Ikaros and Aiolos transcription factors, which in turn results in changed expression of various receptors on the surface of tumor cells. In order to enhance the effectiveness of CAR-based immunotherapy, we assessed the anti-lymphoma efficacy of LEN in combination with CAR19 T cells or CAR20 T cells in vitro and in vivo using various murine models of aggressive B-cell non-Hodgkin lymphomas (B-NHL).Immunodeficient NSG mice were transplanted with various human B-NHL cells followed by treatment with CAR19 or CAR20 T cells with or without LEN. Next, CAR19 T cells were subjected to series of tests in vitro to evaluate their response and signaling capacity following recognition of B cell in the presence or absence of LEN.Our data shows that LEN significantly enhances antitumor functions of CAR19 and CAR20 T cells in vivo. Additionally, it enhances production of interferon gamma by CAR19 T cells and augments cell signaling via CAR19 protein in T cells in vitro. Our data further suggests that LEN works through direct effects on T cells but not on B-NHL cells. The biochemical events underlying this costimulatory effect of LEN are currently being investigated. In summary, our data supports the use of LEN for augmentation of CAR-based immunotherapy in the clinical grounds.
Keywords: tumor immunotherapy; lenalidomide; T cells; Chimeric antigenic receptor; lymphoma